Analysis of strawberry drying behavior under a solar chimney collector using a full factorial method - Ali Serkan Avcı; Aytaç Çetinbaş; Hakan Karakaya (Case Studies in Thermal Engineering, 2025)
In this study, the drying behavior of Albion strawberries was systematically evaluated in a medium-scale solar chimney power plant (SCPP) using a full factorial experimental design. Experiments were performed with 3 mm, 5 mm, 7 mm, and whole strawberry samples placed in four directions (North, South, East, West) and three positions (inlet, middle, near chimney) beneath the collector. Key parameters (temperature, air velocity, moisture content, and drying rate) were monitored throughout process. The SCPP enabled rapid moisture removal, especially at midday, as temperatures exceeded 55 °C and air velocities reached 1.9 m/s. Factorial analysis revealed that time was the most dominant factor affecting both drying rate (73.25 %) and final moisture content (96.71 %), with the Time∗Thickness interaction contributing 20.61 %. The optimum drying condition was observed in the southern section near the chimney with 3 mm slices, achieving complete drying in 270 min. Compared to open sun drying, the SCPP reduced drying time by 70 % in the southern region. Overall, the results show that, by determining the most effective key parameters and optimizing product placement within the collector to prevent any adverse impact on power generation efficiency, the SCPP can effectively dry moisture-rich fruits like strawberries without the need for external energy input.